Floating current-controlled resistance converters using OTAs - Riewruja, Vanchai; Petchmaneelumka, Wandee (My University, 2008)
A simple configuration to realize the floating resistance converters using operational transconductance amplifiers (OTAs) is introduced in this paper. Negative and positive resistances driven by both the voltage and current signals can be achieved in the same scheme. The magnitude of the resulting resistances can be electronically controlled by varying the bias current ratio of OTAs. In addition, the capacitance conversion can be also provided without stability problem. Experimental results verifying the performances of the proposed converters are presented. © 2007 Elsevier GmbH. All rights reserved.
Keywords: Active floating resistor; Current-controlled resistance converter; ECCII; OTA; Simulated resistance